Corrosion Inhibition of Carbon Steel Using Palm Oil Leaves Extract - Nor Insyirah Hairul Salleh; Arman Abdullah (Indonesian Journal of Chemistry, 2019)
Palm oil (Elaeis guineensis) leaves extract was investigated on its potential to inhibit carbon steel corrosion via weight loss and potentiodynamic polarisation methods. Corrosion inhibition of carbon steel using palm oil leaves extract was determined at various temperatures, salinities, and concentrations. The inhibition efficiency increased with the increasing of inhibitor concentration but decreased with the rise in temperature. The highest inhibitor efficiency was 83.70% with a corrosion rate of 0.44 mm/yr which was obtained at zero salinity (in distilled water) with 25% of inhibitor concentration at 303 K. The results obtained proved that the extract solution from palm oil leaves can be used as an effective inhibitor of carbon steel in seawater.